Kepraktisan Model Pembelajaran Investigation Based Multiple Representation (IBMR) dalam Pembelajaran Fisika - Joko Siswanto; Endang Susantini; Budi Jatmiko (Universitas PGRI Semarang, 2016)
This paper presents practicality learning model of IBMR. Its own syntax orientation, investigation, multi representation, aplication, and evaluation. The learning conducted on the fundamental of physics class. At the time of the learning takes place, observations practicality every phase of the learning model IBMR. The results showed that the learning model IBMR has excellent practicality. It shows that every phase of IBMR learning model can be practically implemented